The Relationship of Triage Selection with Length of Stay on Pulmonary TB Patients - Wineiniati, Noni; Riduansyah, Muhammad; Santoso, Bagus Rahmat (GLOBAL HEALTH SCIENCE GROUP, 2024)
Pulmonary TB is a contagious infectious disease that can cause morbidity and death and Indonesia is in second place with the most TB cases (9.2%) globally, so it requires quality services in hospitals. The quality of service for TB patients in the ER with a triage system can be measured through indicators of length of stay. Objective to analyze the relationship between triage selection and length of stay for pulmonary TB patients in the emergency room at Sultan Suriansyah Hospital, Banjarmasin. Quantitative research with analytical survey design and cross sectional approach on 47 respondents selected using purposive sampling technique. Data was taken using observation techniques and analyzed using the chi square test. The majority of respondents were categorized as yellow triage with a total of 23 out of 47 people (48.9%) and were treated for ≥6 hours with a total of 33 out of 47 people (70.2%). The chi square test results show a p value of 0.000 < α 0.05 so that Ha is accepted, which means there is a relationship between triage selection and length of stay for pulmonary TB patients in the emergency room at Sultan Suriansyah Hospital, Banjarmasin. Yellow triage patients have a length of stay that exceeds the average so that the patient's family is expected to be able to understand and hand over nursing actions to professional health workers so that the care provided can run smoothly.